Mapping the research landscape and collaboration networks in waqf knowledge: a bibliometric study - Ismail, Norhidayah; Azis, Saflina; Ismail, Norhisham; Mat, Mustafa Kamal (2025)
Waqf knowledge has gained increasing scholarly attention due to its vital role in fostering public understanding, promoting effective governance, and ensuring the sustainable development of waqf institutions. Despite this growing interest, the intellectual landscape and collaborative dynamics within waqf knowledge research remain underexplored. This study aims to map and visualise the research landscape of waqf knowledge through a bibliometric analysis, using data from the Web of Science (WoS) and Scopus databases, covering the period from 2008 to 2025. Using tools such as RStudio and Biblioshiny, the analysis examines thematic structures, research distribution via treemaps, identifies key sources and prolific authors, and explores collaboration networks among researchers. The findings show that waqf knowledge research focuses on themes such as “Malaysia”, “waqf”, and “developing countries”, while topics like “blockchain” are less explored. The Journal of Islamic Accounting and Business Research emerges as a key publication in this field, whereas journals such as Belleten and Humanomics contribute less frequently, reflecting a concentration of research in a few main outlets. Sukmana, R. and Mohamad, N. are identified as leading authors, while collaboration networks highlight strong clusters, particularly around Laila, N. and Mahphoth, M., with other groups being smaller and more isolated. Identifying influential authors and journals offers valuable guidance for researchers seeking collaboration and publication opportunities. Overall, this study provides a comprehensive map of waqf knowledge research, offering insights to inform future academic pursuits and practical strategies for advancing waqf knowledge. Future research should incorporate keyword co-occurrence and citation analyses to reveal deeper thematic connections and conceptual developments within the field.